English words in Bangla speeches and conversations: An analysis of their influence on Banglain Bangladesh - Hoque, Muhammad Azizul (IIUC Studies, 2026)
English now serves as a global communication tool for diverse people and purposes, not just native speakers. Bangladesh borrows, code-switches, code-mixes, transliterates, and uses the language like other countries. As observed in writings, Bangladeshi multi-professionals also often use English lexicon in Bangla speeches and conversations. The phenomenon appears to have received little scholarly attention. Therefore, the current researcher has closely observed multi-professional conversations and speeches to determine how English lexical components affect Bangla spoken texts. Purposive sampling was used to select 42 multi-professional speeches and conversations for this study. The recorded data were analyzed using quantitative content analysis. The findings reveal the presence of English lexical elements of various natures in the daily speeches and conversations of Bangla speakers. This paper shows that while redundant, some English vocabulary components can make Bangla verbal communication livelier. To determine how English words affect Bangla, 17 academics were interviewed. Interview data were thematically analyzed. This paper aims to discuss the importance of language awareness, which can influence language policy and use in Bangladesh by focusing on the functions of both the native (Bangla) and foreign (English) languages. IIUC Studies, Vol.-21, Issue-1, Dec. 2024, pp. 9-40